2009
DOI: 10.1364/oe.17.018330
|View full text |Cite
|
Sign up to set email alerts
|

Frequency tunable near-infrared metamaterials based on VO_2 phase transition

Abstract: Engineering metamaterials with tunable resonances from mid-infrared to near-infrared wavelengths could have far-reaching consequences for chip based optical devices, active filters, modulators, and sensors. Utilizing the metal-insulator phase transition in vanadium oxide (VO(2)), we demonstrate frequency-tunable metamaterials in the near-IR range, from 1.5 - 5 microns. Arrays of Ag split ring resonators (SRRs) are patterned with e-beam lithography onto planar VO(2) and etched via reactive ion etching to yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
352
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 512 publications
(361 citation statements)
references
References 32 publications
3
352
1
1
Order By: Relevance
“…119 Combinations of Ag and VO 2 have also been explored for invoking tunable thermochromism of the near-infrared optical properties by use of metamaterials employing Ag/ VO 2 hybrid split-ring resonators. 120 From a practical point of view, VO 2 may be awkward to prepare since the vanadium ions are in states with intermediate oxidation and it may be more facile to fabricate materials under nonoxidizing ͑metallic V͒ or fully oxidizing ͑in-sulating V 2 O 5 ͒ conditions. The limitations are not as stringent as they may seem, though, and it should be observed that metallic vanadium can be transformed to VO 2 by controlled oxidation [121][122][123][124] and that insulating V 2 O 5 van be transformed to VO 2 by controlled reduction in films.…”
Section: Discussionmentioning
confidence: 99%
“…119 Combinations of Ag and VO 2 have also been explored for invoking tunable thermochromism of the near-infrared optical properties by use of metamaterials employing Ag/ VO 2 hybrid split-ring resonators. 120 From a practical point of view, VO 2 may be awkward to prepare since the vanadium ions are in states with intermediate oxidation and it may be more facile to fabricate materials under nonoxidizing ͑metallic V͒ or fully oxidizing ͑in-sulating V 2 O 5 ͒ conditions. The limitations are not as stringent as they may seem, though, and it should be observed that metallic vanadium can be transformed to VO 2 by controlled oxidation [121][122][123][124] and that insulating V 2 O 5 van be transformed to VO 2 by controlled reduction in films.…”
Section: Discussionmentioning
confidence: 99%
“…When a THz metallic SRR array was fabricated directly on top of a strontium titanate (STO) substrate (a phase transition material), the resonance frequency experiences a red-shift when decreasing the temperature, due to the increasing refractive index of the STO substrate, although it suffers from significant insertion loss due to the high refractive index of the STO substrate [199]. Vanadium dioxides (VO 2 ) is another thermally driven insulator-to-metal phase transition material that has attracted great interest in realizing thermally active metasurfaces at THz and infrared frequencies [200][201][202][203][204][205]. The nonvolatile thermally switchable metasurface response has potential applications such as memory devices [201], and the metasurface resonance can be also switched through the application of a voltage bias [198].…”
Section: Other Resonance Switchable and Frequency Tunable Metasurfacesmentioning
confidence: 99%
“…1 Phase-change materials, including chalcogenides, [2][3][4][5] vanadium dioxide, [6][7][8] gallium, 9 and liquid crystals, [10][11][12] have featured prominently in this evolution. We now show that the chalcogenides offer a uniquely flexible platform for the realization of non-volatile, optically-switchable alldielectric metamaterials.…”
mentioning
confidence: 99%